Estimation of reservoir temperature and analysis of the mechanism of origin of a granite dome-controlled geothermal system in the western Wugongshan area, southeast China - Wang, Luyao; Liu, Kai; Zhang, Shouchuan; Zhang, Yaoyao; Jia, Wuhui; Yu, Tingxi; Guo, Junhan (Frontiers in Earth Science, 2023)
The escalating issues of worldwide energy scarcity and environmental contamination have brought geothermal resources into the spotlight as a sustainable and eco-friendly energy alternative. The circum-Wugongshan geothermal belt has the abundant geothermal resources with the medium-low temperature, which has significant potential for development and utilization. In this study, the samples of geothermal groundwater, cold spring and surface water were collected from the western Wugongshan area. The hydrochemical and thermodynamic methods were used to estimate the reservoir temperature and analyze the genetic mechanism. The analysis results indicate that: The hydrochemical characteristics of most geothermal groundwater are Na-HCO3 and Na-SO4, while these of cold springs and surface water are Na-HCO3 and Ca-HCO3, respectively. Quartz and multicomponent geothermometers provide more reliable estimation of reservoir temperatures, ranging from 64.8 °C to 93.4 °C. The circulation depth of geothermal water circulates ranges from 1729.3 m to 2292.5 m. The mixing model indicates that shallow cold water is blended at a rate of 62.1% to 78.8%. The δD and δ18O values validate that the geothermal water originates from atmospheric precipitation, with recharge elevations varying between 503.1 m and 1375.6 m. Based on the above analysis, a conceptual model is proposed to reveal the mechanism of geothermal groundwater genesis.